Hashimoto’s Thyroiditis: A “Double-Edged Sword” in Thyroid Carcinoma - Xu, Jiangyue; Ding, Ke; Mu, Lan; Huang, Jiangsheng; Ye, Fei; Peng, Yu; Guo, Can; Ren, Chutong (Frontiers in Endocrinology, 2022)
Background: The prevalence of thyroid carcinoma (TC) and Hashimoto’s thyroiditis (HT) has been increasing dramatically over the past these decades. We investigated the relationship between HT and TC. Methods: We followed the Meta-analysis of Observational Studies in Epidemiology (MOOSE) guidelines for carrying out and reporting this meta-analysis. The literature from 1 January 2010 to 31 December 2020, regardless of region and publication type, was searched comprehensively in PubMed, Embase, Web of Science, and Cochrane Library databases. After careful selection and data extraction, the pooled odds ratio of various clinical characteristics in 39 studies were calculated. Publication bias was analyzed using funnel plots. Results: Meta-analysis of 39 original-research articles studies showed HT to be a risk factor of TC (pooled odds ratio = 1.71, 95% confidence interval 1.57–1.80, p < 0.00001) and papillary thyroid carcinoma (1.67, 1.51–1.85, < 0.00001). Patients with papillary thyroid carcinoma (PTC) combined with HT were more likely to have multifocal carcinomas. The prevalence of an extrathyroidal extension, metastasis, BRAFV600E mutation, and recurrence was significantly lower in patients with PTC combined with HT. Conclusions: HT is a “double-edged sword” in TC patients. HT increases the risk of TC and PTC but is a protective factor against PTC progression.